Cover Feature: Influence of Substituents in the Benzene Ring on the Halogen Bond of Iodobenzene with Ammonia (ChemPhysChem 6/2022). Issue 6 (18th March 2022) - Scheiner, Steve; Hunter, Sarah
Abstract : The Cover Feature depicts the effect of substituents placed ortho, meta, and para to the iodine atom on various aspects of this halogen bond (XB). Electron‐withdrawing groups strengthen the XB, particularly those placed in an ortho position. The bond strength correlates with the NMR chemical shift of the N and C atoms, as well as the JIN coupling constant. More information can be found in the Research Article by Steve Scheiner and Sarah Hunter .